Canadian Evaluation Society Tribute to Dr. Michael Scriven - Love, Arnold (Journal of MultiDisciplinary Evaluation, 2024)
During his long career, Dr. Michael Scriven made significant contributions to building the evaluation profession in Canada. The Canadian Evaluation Society recognized Dr. Scriven with an In Memoriam sent in the CES Newsletter to all CES members on September 25, 2023. This article contains the substantive content of the tribute to Michael Scriven by the Canadian Evaluation Society. Published with the permission of the Canadian Evaluation Society and the Canadian Journal of Program Evaluation/La Revue canadienne d'evaluation de programme.